Optimizing Economic Dispatch through Web-based Applications using Lambda Iteration Algorithm for Efficient Power System Operation - Muhammad Fadli Azis; Mutmainnah; Lutfi; Julianti Habibuddin (Department of Electrical Engineering, Faculty of Engineering, Universitas Negeri Surabaya, 2023)
This research presents the development of an online economic dispatch web application using the lambda iteration method. The proposed method is implemented through a systematic process of problem formulation, optimization method selection, application design, and testing. The web application is created using MATLAB Web Apps and tested using generation data from the IEEE 30 bus system. The results demonstrate that the developed web application operates effectively and fulfills the desired specifications. Users can access the application via web browsers without the need for MATLAB installation on their devices. The study concludes that the developed economic dispatch web application can serve as a valuable tool for enhancing the efficiency and effectiveness of economic dispatch processes. The application can be further optimized by incorporating more comprehensive and user-friendly features.